Emerging Delivery Systems for Enabling Precision Nucleic Acid Therapeutics - Bian, Xiaochun; Zhou, Liping; Luo, Zhiwei; Liu, Guotao; Hang, Zhongci; Li, Haohao; Li, Fengyong; Wen, Yongqiang (ACS nano, 2025)
Nucleic acid therapeutics represent a highly promising treatment approach in modern medicine, treating diseases at the genetic level. However, these therapeutics face numerous challenges in practical applications, particularly regarding their stability, effectiveness, cellular uptake efficiency, and limitations in delivering them specifically to target tissues. To overcome these obstacles, researchers have developed various innovative delivery systems, including viral vectors, lipid nanoparticles, polymer nanoparticles, inorganic nanoparticles, protein carriers, exosomes, antibody oligonucleotide conjugates, and DNA nanostructure-based delivery systems. These systems enhance the therapeutic efficacy of nucleic acid drugs by improving their stability, targeting specificity, and half-life in vivo. In this review, we systematically discuss different types of nucleic acid drugs, analyze the major barriers encountered in their delivery, and summarize the current research progress in emerging delivery systems. We also highlight the latest advancements in the application of these systems for treating genetic diseases, infectious diseases, cancer, brain diseases, and wound healing. This review aims to provide a comprehensive overview of nucleic acid drug delivery systems’ current status and future directions by integrating the latest advancements in nanotechnology, biomaterials science, and gene editing technologies, emphasizing their transformative potential in precision medicine.